Clinical and Financial Implications of Second-Opinion Surgical Pathology Review: Experience of a Comprehensive Cancer Center With Regional Affiliates. Issue 4 (26th March 2021) - Johnson, Steven M; Samulski, Teresa D; O'Connor, Siobhan M; Smith, Scott V; Funkhouser, William K; Broaddus, Russell R; Calhoun, Benjamin C
Abstract: Objectives: Second-opinion pathology review identifies clinically significant diagnostic discrepancies for some patients. Discrepancy rates and laboratory-specific costs in a single health care system for patients referred from regional affiliates to a comprehensive cancer center ("main campus") have not been reported. Methods: Main campus second-opinion pathology cases for 740 patients from eight affiliated hospitals during 2016 to 2018 were reviewed. Chart review was performed to identify changes in care due to pathology review. To assess costs of pathology interpretation, reimbursement rates for consultation Current Procedural Terminology billing codes were compared with codes that would have been used had the cases originated at the main campus. Results: Diagnostic discrepancies were identified in 104 (14.1%) patients, 30 (4.1%) of which resulted in a change in care. In aggregate, reimbursement for affiliate cases was 65.6% of the reimbursement for the same cases had they originated at the main campus. High-volume organ systems with low relative consultation reimbursement included gynecologic, breast, and thoracic. Conclusions: Preventable diagnostic errors are reduced by pathology review for patients referred within a single health care system. Although the resulting changes in care potentially lead to overall cost savings, the financial value of referral pathology review could be improved.